Research on the effect of LAMP1 in the development and progression of ccRCC and its potential mechanism with LC3C-mediated autophagy - Wang, Xiongbao; Fang, Liang; Xiao, Lixiang; Zhong, Guangxin; Han, Minghao; Wang, Bingshen; Ren, Juchao; Zang, Yuanwei (Frontiers in Immunology, 2024)
BackgroundLysomembrane-associated protein 1 (LAMP1), known to exhibit differential expression in various tumor types and play a crucial role in the development of tumors. Clear cell Renal Cell Carcinoma (ccRCC) is still the most common pathological type of renal carcinoma with poor prognosis. However, the expression of LAMP1 and its underlying molecular mechanism with ccRCC remain elusive.MethodsFirstly, the expression of LAMP1 in ccRCC and its clinical significance were analyzed using various databases. Next, Weston Blot was performed to detect the expression of LAMP1 protein in cancer tissues and adjacent tissues from 60 pairs of clinical ccRCC patients. The correlation between LAMP1 expression and different clinical indicators as well as the relationship with patient prognosis was analyzed. Furthermore, molecular cell biology experiments were conducted to validate the effects of LAMP1 gene expression on cell proliferation, invasion and migration. Additionally, we investigated the impact of VHL, a key gene in renal cancer, and LC3C, an autophagy-related gene, on LAMP1 expression through molecular biology experiments to elucidate the potential underlying mechanism.ResultsBioinformatics analysis revealed significant underexpression of LAMP1 in ccRCC (P<0.001), which correlated with poorer prognosis. In multivariate survival analysis, LAMP1 emerged as an independent prognostic marker for overall survival(OS)(P<0.05). Analysis of cancer and paracancer tissue samples from ccRCC patients demonstrated significantly lower levels of LAMP1 in tumors compared to paracancerous tissues (P<0.001), confirming its prognostic impact. Cell functionality experiment revealed that elevated LAMP1 inhibited cell proliferation, migration, and invasion. LAMP1 expression remained unchanged during autophagy modulation but decreased with LC3C knockdown and vice versa. Notably, VHL(+) cells expressed less LAMP1 than VHL(-) cells.ConclusionsThese findings indicate that low expression levels of LAMP1 is associated with poor prognosis in ccRCC. Therefore, LAMP1 emerges as a novel biomarker associated with the diagnosis and prognosis of renal cancer. Furthermore, we have also described the potential mechanism of action of LAMP1 in renal cancer. LAMP1 is a promising target for the treatment of ccRCC.